The planning of training process in triathlon - Водлозеров, Владимир Егорович (Slobozhanskyi Herald of Science and Sport, 2016)
Vodlozerov V. Purpose: is the working out of base variant of training process as the base for planning of individual training of triathlete. Material & Methods: studying and generalization of special literature of basis training process for endurance in cyclic kinds of sports, the analysis of training of famous triathletes to competitions. Results: mane stages of training process formation in triathlon and features of distribution of sportsman’s training load in depending on period of training were considered. Conclusions: comprehensive planning of training process in different kinds of triathlon is lying down in basis of improving of competition form of triathlete.